In vitro α-amylase and hemoglobin glycation inhibitory potential of Nigella sativa essential oil, and molecular docking studies of its principal components - Dalli, Mohammed; Daoudi, Nour Elhouda; Abrigach, Farid; Azizi, Salah-eddine; Bnouham, Mohamed; Kim, Bonglee; Gseyra, Nadia (Frontiers in Pharmacology, 2022)
Nigella sativa is plant that is endowed with various pharmacological activities including antioxidant, anticancer, anti-inflammatory, antibacterial, antidiabetic, and immunostimulant. This study aims to investigate the antidiabetic activity of the Nigella sativa essential oil on two key enzymes the α-amylase and hemoglobin glycation. After the extraction procedure, the Nigella sativa essential oil, were subject to qualitative and semi-quantitative analysis using GC/MS, for the identification of the different bioactive compounds. This was followed by an evaluation of the in vitro inhibition capacity of the α-amylase and the hemoglobin glycation. Finally, a molecular docking study was conducted to determine the bioactive compounds responsible for the antidiabetic activity. The extracted essential oil showed the presence of different bioactive compounds including α-phellandrene (29.6%), β-cymene (23.8%), 4-caranol (9.7%), thymol (7%). The Nigella sativa essential oil was found to be endowed with an antiradical scavenging activity with an IC50 of (7,81 ± 0,08 mg/ml), and to have a ferric reducing activity with an IC50 value of (7,53 ± 0,11 mg/ml). The IC50 value for the α-amylase inhibitory activity was 0.809 mg/mL, indicating an inhibitory impact of the enzyme. The IC50 value for the Nigella sativa essential oil's hemoglobin antiglycation activity was 0.093 mg/mL. For most predominating phytochemicals present in the Nigella sativa essential oil, molecular docking studies against human pancreatic α-amylase and human hemoglobin enzymes revealed that these compounds can serve as lead molecules to develop new antidiabetic compounds.